A Cyber Security Analysis Used for Unmanned Aerial Vehicles in the Smart City - Sumeyye Cebeloglu, F.; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2019)
Unmanned aerial vehicles (UAVs) are devices that carry the appropriate equipment and have automatic management with software or via remote control. The use of UAVs in civil, military and scientific fields is rapidly becoming widespread throughout the world. The reason for this increasing demand for UAVs is that it has a wide usage area and reduces errors, costs, time and labor. With its advantages, it seems that it will increasingly occupy agendas of national. With today's technological developments, smart cities benefit from UAVs. In addition to the advantages of using UAVs in daily life, it also causes some problems. The most important of these is the security problem. Safety vulnerability during the use of UAVs can lead to the loss of money and time and can disrupt the reputation of the city and the country. The aim of the study is to analyze the cyber attacks that UAVs may encounter with the use of UAVs in smart city applications and to make recommendations for preventing such attacks. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: cyber security; smart city; unmanned airal vehicles